A case of heat-related illness - Sheng, Chew keng; Latif, Abdul kursi abdul (2011)
Although heat-related illnesses are relatively uncommon in the UK, nonetheless, this can pose serious dangers to military personnel posted to the Middle East as well as tourists who are not acclimatised to the hot weather of a tropical country. This article illustrates some common presentations of heat-related illnesses by highlighting the case of a man who suffered from heat exhaustion after he lost consciousness in his car. This case happened in the authors' home country, Malaysia.